A disfunção temporomandibular, representações sociais no contexto da odontologia - Costa Filho, Jairton (2023)
Temporomandibular disorder (TMD) refers to conditions that affect the temporomandibular joint (TMJ) and/or the musculature involved in the masticatory process. Its etiology is multifactorial, controversial and not yet fully understood. Individuals with TMD present several alterations caused by excessive forces, parafunctional habits, inflammatory processes, degenerative morphological alterations, infectious processes, genetic, psychological and anatomical factors. In this context, we sought to study the theme through the Theory of Social Representations (TSR), which made it possible to access the network of senses and meanings, shared by university students of dentistry. Specifically, to identify the scientific production subsidized by the Theory of Social Representations (TRS), about Quality of Life and Temporomandibular Disorders; identify the sociodemographic profile of the research participants; analyze temporomandibular disorders from the psychosocial point of view of dentistry students and understand the anchorages of temporomandibular disorders elaborated by dentistry students. Structurally, this thesis was divided into two parts, the first consisting of theoretical chapters and the second consisting of three articles. In the first article, a systematic review was carried out supported by the Theory of Social Representations (TRS), about Quality of Life and Temporomandibular Disorders. The sample consisted of 11 articles, which were processed by the Iramuteq software and analyzed by Descending Hierarchical Classification (CHD) and Similitude. The results indicated representative psychosocial aspects of becoming ill, such as discomfort and crepitation in the TMJ region, headache, stiffness, difficulty opening the mouth without arousing pain. Among these elements, pain was considered the figurative element of objectification, anchored by socio-psychological and organic physical factors. The other two studies were empirical, guided by TRS. The first empirical study aimed to analyze temporomandibular disorders from a psychosocial perspective by Dentistry students. The study included 151 Dentistry students aged between 18 and 35 years (M= 25.68; SD= 11.6), who answered a biosociodemographic questionnaire and an in-depth interview. The collected material constituted a textual corpus, which were processed by ALCESTE, IRAMUTEQ and SPSS software (version 21). The contents coming from the software were analyzed by Descending Hierarchical Classification (CHD) and Similitude. and through descriptive statistics. It was observed that the participants pointed out in their social representations, knowledge about temporomandibular disorders, highlighting the diagnosis, e.g. treatment were also anchored in physiological and psychological factors, which were permeated by negative emotions (stress, anxiety). The participants ratified notions of responsibilities, focused on the consequences of the disease, such as the daily maintenance of palliative treatment, understanding that it is a chronic disease. The results point to the importance of an interdisciplinary approach that focuses on psychosociological support, aimed at the elaboration 10 of strategies that can be adopted in the face of the control and care of temporomandibular disorders. The second empirical study, with the participation of 151 Dentistry students, aged between 18 and 35 years (M= 25.68; SD= 11.6), aimed to know the SR of temporomandibular disorders from the perspective of the students of dentistry. Data were processed by SPSS (version 21) and Tri-deux-mots software. It is noteworthy that the SR on the impact of temporomandibular disorder on the quality of life of university students of dentistry acquired different facets, therefore, it is expected that the results discussed through the research and in the light of the literature, will contribute to professionals in the area pointing out its applicability and suggesting the consequences of future research and interventions. It is suggested the need to expand the N sample, data collection in person, as well as the use of other instruments.